INFERENCE OF READING LITERACY GAP BETWEEN ELEMENTARY SCHOOL AND ISLAMIC ELEMENTARY SCHOOL BASED ON THE PIRLS FRAMEWORK - Iftha Nur Sutanti; Hidayaturrohmah; Abdul Wachid Bambang Suharto (Journal of Language and Literature Education, 2026)
Reading literacy achievement among Indonesian elementary students remains critically low, with notable disparities between Elementary Schools (SD) and Madrasah Ibtidaiyah (MI). This issue is structurally embedded within Indonesia's dual education system. Existing studies have largely examined reading literacy in general, with limited attention to comparative analysis between SD and MI using international benchmarks. This study aims to critically examine the inferred literacy gap between SD and MI based on the Progress in International Reading Literacy Study (PIRLS) framework, using a qualitative approach through a systematic literature review of thirty scholarly sources published between 2011 and 2026. The findings indicate that both SD and MI students demonstrate significant weaknesses in higher-order reading comprehension processes, particularly in inferencing, interpretation, and evaluation. This gap is more pronounced in MI due to five structural factors: reading teacher shortage, resource allocation disparity, dual-curriculum burden, lower socioeconomic background of students, and cognitive complexity from Arabic-medium instruction. Drawing on educational equity theory and Bourdieu's framework of cultural and institutional capital, this study concludes that bridging the SD–MI literacy gap requires differentiated yet integrated policy responses, including the development of MI-specific literacy programs, targeted teacher training, and the systematic inclusion of MI in future national and international literacy assessments.